Antioxidant Potential and Type II Diabetes Related Enzyme Inhibition Properties of Raw and Processed Legumes in Indian Himalayas - Dibyendu Talukdar (Journal of Applied Pharmaceutical Science, 2013)
In vitro antioxidant potential and type II diabetes related enzyme inhibition capacity was analyzed in methanolic extract of raw and processed seeds of seven prominent legume genotypes, originated in Indian Himalayas. In raw seeds, total free phenolic content ranged from 2.18 ± 1.9 (small-seeded urd bean) to 13.11 ± 2.4 (bold-seeded grass pea) mg gallic acid/g extract dry weight basis (dwb), while total flavonoids varied between 1.89 ± 0.61(lima bean) and 0.41 ± 0.9 (small-seeded urd bean) mg catechin/ g of the extracts, dwb. Raw seed extracts exhibited scavenging capacity against DPPH (30.80 - 66.40 %), superoxides (43.78-71.22%) and hydrogen peroxide (11.19-53.78%) along with ferric reducing/antioxidant power (FRAP, 37.87-161.32 µmol/g extract dwb) and inhibition of ß-carotene degradation (23.45-49.11%). In type II diabetes related enzyme inhibition activity, the value varied from 8.11% (urd bean) to 21.34% (lima bean) for α-amylase and from 27.12% (urd bean) to 87.54% (grass pea) for α-glucosidase in raw seed extracts under in vitro bioassay. Among the processing methods, sprouting followed by direct cooking showed significant enhancement of antioxidant activity along with balanced levels of enzyme inhibition capacity, while soaking + cooking as well as roasting showed diminishing effects. Oil-frying exhibited mixed effects. Bold-seeded lima bean, grass pea and black-seeded common beans were superior to lentil, small-seeded urd bean and white-seeded beans. Phenolic content was correlated with antioxidant properties and enzyme inhibition activity, but this association was stronger in sprouting and direct cooking than raw seeds and other three methods.
Keywords: &alpha; -Amylase inhibition, Antioxidant activity